'We Have Given Birth to a Very Busty Infant': Post-War Origins of Sports Medicine in New Zealand. Issue 12 (13th August 2021) - Hamilton, Bruce; Ryan, Greg
Abstract: Despite growing interest in the origins of sports medicine, there has been little academic attention paid to the development of healthcare in New Zealand sport. Using primary archival sources as well as contemporaneous literature from the post-world war period to the founding of the New Zealand Federation of Sports Medicine (NZFSM) in 1963, this manuscript addresses this knowledge gap. By the mid-twentieth century, public health in New Zealand had evolved from focussing on infectious disease control to the challenges of non-communicable illnesses such as heart disease and obesity. Internationally, the development of sports medicine was seen as one tool to promote healthy lifestyles and by the mid-1950s many countries with similar sport and health ideologies had established sports medicine organizations. The modern Olympic games played a significant role in the evolution of sports medicine. However, relative to many countries New Zealand's incorporation of sports medicine into Olympic teams was delayed, and it was not until 1960 that a physiotherapist was informally embedded into the Olympic team. Ultimately, a group of like-minded doctors, brought together by an evolving social, political, sporting and medical milieu, established the NZFSM, eventually leading to sports medicine being professionally recognized, multi-disciplinary and routinely practiced in New Zealand.